2023
DOI: 10.1108/agjsr-09-2022-0178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution of wheat flour with chickpea flour on their physico-chemical characteristics

Abstract: PurposeThe major objective of this research work was to evaluate various physico-chemical characteristics, such as, chemical composition, antioxidant capacity, objective color and texture profile analysis (TPA) of the wheat flour/chickpea flour (CF) blends, so that nutritious baked products could be consumed by the type-2 diabetic persons.Design/methodology/approachWholegrain wheat flour (WGF) and white wheat flour (WWF) were substituted with CF at 0 to 40% levels. These wheat flour/CF blends were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…F4 exhibits the greatest hardness value among the samples, at 8.34 N. In contrast, F3 is the sample showing the minimum hardness value, measuring 1.47 N. The statistical analysis findings indicate no significant differences among the samples. The term "hardness" is operationally defined as the highest recorded force, measured in Newtons, seen during the initial compression cycle of the dough (Sidhu et al, 2023). The hardness value of the flakes examined in this study was lower than that of brown rice flakes, which was reported to range from 72.01 N to 510.80 N (Huang et al, 2023).…”
Section: Texture Analysismentioning
confidence: 79%
See 1 more Smart Citation
“…F4 exhibits the greatest hardness value among the samples, at 8.34 N. In contrast, F3 is the sample showing the minimum hardness value, measuring 1.47 N. The statistical analysis findings indicate no significant differences among the samples. The term "hardness" is operationally defined as the highest recorded force, measured in Newtons, seen during the initial compression cycle of the dough (Sidhu et al, 2023). The hardness value of the flakes examined in this study was lower than that of brown rice flakes, which was reported to range from 72.01 N to 510.80 N (Huang et al, 2023).…”
Section: Texture Analysismentioning
confidence: 79%
“…Flakes with a lower protein (F1) concentration exhibit a greater capacity for water absorption, resulting in increased stickiness and decreased hardness. There is a negative correlation between higher hardness and adhesiveness (Sidhu et al, 2023;Sozer & Kaya, 2003). This implies that the texture of soft flakes (F1) will exhibit adhesive properties.…”
Section: Texture Analysismentioning
confidence: 99%